Una breve historia de la educación contable en Colombia (2017)
This document aims to address the issue of accounting education from the approach of skills and competencies in the process of training and professionalization in the framework of accounting knowledge. It proposes as perspective in the accounting discipline, strategic and global variables of research, critical and participative analysis with professional and competitive qualities, from missionary (and curricular) scenarios of formal and non-formal education institutions.